Strategies to improve human resource performance at PT XYZ in West Java - Priyono, Adi (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to identify factors that affect human resource performance at PT XYZ and determine strategies needed to improve HR performance. This study is based on the Sink and Tuttle's strategic approach, namely, effectiveness, efficiency, quality, productivity, quality of work life, innovation and profitability. The study was conducted at the company's operational locations in plantations and tea processing factories as well as at the head office and representatives of the company in West Java. Data collection is carried out from April 2023 to September 2023, with data collected from January 2020 to October 2023 through interviews using questionnaires. The results of measuring human resources performance using the AHP, OMAX and TLS methods above have shown KPIs that are not achieved in the criteria for achieving HR performance at the plantation. The weak factors in influencing the non-achievement of HR performance are (1) Factory output productivity ratio; (2) Factory utility ratio; (3) Labor cost ratio in the plant; (4) Labor costs in the factory; (5) Material / Material Cost ratio; (6) General and administrative cost ratio. The Shoot Analysis Percentage will be suitable for the implementation of strategies to increase supervision and adjust SOPs or rules related to shoot analysis. The drone mapping (mapping) of plant health and populations can also be useful to find out plant health from above the satellite / drone, so that a more appropriate solution can be found for the process of health or recovery of gardens.